Historic Basis for the Modern Robotic Approach to the Anatomic and Physiologic Reconstruction Hiatal Hernias - Gharagozloo, Farid; Ware, Amendha (British Journal of Healthcare and Medical Research, 2022)
A hiatal hernia is a common clinical entity which has been the subject of great controversy for over a century. During this time, medical practitioners have been like “blind” men who have examined the different parts of an elephant and reached a conclusion based on the partial knowledge but have been unable to recognize the “whole elephant”. The robotic approach to the repair of Hiatal Hernias which not only incorporates the technology of robotics but is designed to return the anatomy and physiology of the hiatus to its normal function, is the culmination of the work of many surgical giants who independently identified specific parts of the “elephant” that is represented by the entity of a Hiatal Hernia. The Robotic Anatomic and Physiologic Repair of the Hiatal Hernia is also the result of a greater understanding of the very complex normal and pathologic physiology of the esophageal hiatus. Investigators from 5 specialties (cardiology, gastroenterology, pulmonary medicine, surgery and radiology), using multiple modalities such as echocardiography, computed tomography, exercise testing, respiratory function testing, have shed new light into the pathophysiology and surgical indications for the repair of Hiatal Hernias. An Understanding of the history of the surgical treatment of Hiatal Hernias sheds light on the controversies and misunderstandings that have characterized the surgical approach to this very important condition.